Habitat occupancy patterns and activity rate of native mammals in tropical fragmented peat swamp forests - Selvadurai, Sasidhran (2016)
The North Selangor Peat Swamp Forest (NSPSF) is the second largest remaining peatland fragment in Peninsular Malaysia. Although the NSPSF is recognized as a biodiversity hotspot area in the region, this peat swamp forest is rapidly shrinking mainly due to the expansion of industrial oil palm cultivation. More than 87% of the NSPSF was designated as forest reserves, but in reality, this current status is not really similar to a protected area. This peat swamp forest is still under constant threats from forest conversions, forest fires, and road constructions. Faunal biodiversity loss is likely to happen in the NSPSF unless drastic action is taken by stakeholders. To determine the habitat occupancy and activity rate of various mammals, camera-trap survey was conducted at 45 points located within the NSPSF. From a total survey effort of 2,565 trap nights in an area of 778 km²,16 mammal species were recorded. However, there were no records of Sumatran rhinoceros (Dicerorhinus sumatrensis) and Malayan tiger (Panthera tigris) or indirect sightings such as footprints, suggesting possibility of being locally extinct at this peat swamp forest. The mammal activity rate responded differently to in situ habitat quality and landscape factors according to their feeding guild or diet. The data from camera trap sampling provides vital information on the occurrence of high conservation wildlife species in the NSPSF. It is recommended that conservation agencies to consistently monitor clearance of the forest, create a blueprint to mitigate the post-clearance effects and develop a camera-trapping survey to monitor the mammal populations. Government stakeholders should focus on prohibiting further conversion of peat swamp forests and emphasize on the conversion of the NSPSF status from a forest reserve to a protected area.